Pengaruh Self-Efficacy dan Motivasi Kerja Terhadap kinerja Pegawai Sekretariat DPRD Kota Medan - Nassyiatul Aisyiyah; Kaiman Turnip; Nina Siti Salmaniah Siregar (Mahesa Research Center, 2022)
The purpose of this study was to analyze the effect of self-efficacy and work motivation on employee performance at the secretariat of the medan city DPRD, the research desaign was a quantitative approach with a descriptive verification method, the sample used in this studywere are civil servants in the secretariat office of the medan city DPRD, namely 50 employees, except for civil servant appraisers, the sampling technique is probability sampling with purposive sampling technique, data analysis is carried out with multiple linear regression, the most dominan variable effecting employee performance is work motivation variable while self-efficacy variable does not significantly affect employee performance at the secretariatt of the city DPRD medan, besides that, self-efficacy and work motivation simultaneosly affect the performance of employees at the secretariat of the medan city DPRD.